MODEL KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU DI SMA N 1 TERBANGGI BESAR LAMPUNG TENGAH - Nuryanti, Titik; Adib, Abdul; Sunarto, Sunarto (UNISAN JURNAL, 2023)
The principal's leadership model has an important role in improving teacher competence. The purpose of this study was to find out the principal's program in increasing teacher competence, the principal's strategy in increasing teacher competence and the principal's policy in increasing teacher competence. The approach used in this study is a qualitative approach with descriptive methods. Data collection techniques were carried out by interviews, observation, and documentation studies. The subjects in this study were school principals, deputy principals, senior teachers/chairmen of the MGMP, and teachers. The results of the study show that: (1) The principal's program is structured as a reference in increasing teacher competence, which is carried out in empowering teachers. The teacher empowerment program is carried out by involving teachers in school decision making and also by training teachers to be responsible for school development. The principal in formulating the program involves all teachers and school staff. (2) The school principal's strategy in improving teacher competence is carried out by the school principal through several efforts, including developing skills training for teachers, providing motivation and fostering the discipline of education staff. (3) The principal's policy in improving teacher competency is carried out by involving teachers in developing the school's vision and mission, school goals, and formulating the school curriculum. The school principal provides opportunities for teachers to participate actively, openly and cooperate in realizing the school's vision